Challenging Construction Projects Related to Urban Tunnels - R. Katzenbach; S. Leppla (Geotechnical Engineering Journal of the SEAGS & AGSSEA, 2024)
The growing size and population density of metropolitan areas and the along going traffic demands lead to the construction of large infrastructure projects. In many cases these infrastructure projects are close to sensitive properties. The construction of new underground structures and the deconstruction of existing structures often have a significant influence on existing (underground) structures. The experiences of two large projects from Spain and Germany will be presented in the paper. The first of the presented projects is the new tunnel of the Spanish high speed railway line under the city centre of Barcelona, Spain. The tunnel boring machine (TBM) with a diameter of 11.55 m passed next to two buildings that belong to the World Heritage Properties of the UNESCO. The second project is the deconstruction of an up to 14 storeys high building in Frankfurt am Main, Germany. Under the deconstructed building are an underground station and tunnels of the urban metro system. The uplift and deformation of the underground structures had to be limited to guarantee the serviceability of the sealing. The paper focuses on the extensive geotechnical and geodetic measurement programs that were installed regarding the observational method and the measurement results. The experiences made in the planning and construction phases of these complex projects are explained and for new inner urban projects recommendations are given. In order to reduce the subsidence risk, earth pressure balanced shield machines are a good solution in an urban environment in comparison to other tunnelling methods. Settlements are evoked by changes in the stress conditions or changes in pore water pressure.